2009
DOI: 10.1590/s0004-27302009000900011
|View full text |Cite
|
Sign up to set email alerts
|

Low false-negative rate of cytology in thyroid nodules > 4 cm

Abstract: Objective: To report the results of cytology and histology obtained for a series of systematically resected thyroid nodules ≥ 4 cm. Methods: A group of 151 patients with thyroid nodules ≥ 4 cm was submitted to surgery despite the cytology result. Results: Malignancy was confirmed histologically in 22.5% of the patients. Excluding cases of insufficient material, cytology was benign in only 3/31 carcinomas (90.3% sensitivity). The frequency of malignancy was 35% among nodules with indeterminate cytology (follicu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 12 publications
4
37
2
Order By: Relevance
“…Several studies have assessed the relationship between thyroid nodule size and FNA accuracy as well as the false‐negative rates. Carrillo et al and McCoy et al reported false‐negative rates for thyroid nodules ≥4 cm that were higher than our findings (20.0% and 12.7%, respectively), whereas Kuru et al, Rosario et al, and Kamran et al reported FNR (false‐negative rates) lower than found in our data (4.3%, 3.6%, and 1.3%, respectively). Other studies have shown similar findings which were either higher or lower than the findings on the false negative rates in our study Porterfield et al, Shrestha et al, Carrillo et al, and Meko and Norton .…”
Section: Discussioncontrasting
confidence: 88%
“…Several studies have assessed the relationship between thyroid nodule size and FNA accuracy as well as the false‐negative rates. Carrillo et al and McCoy et al reported false‐negative rates for thyroid nodules ≥4 cm that were higher than our findings (20.0% and 12.7%, respectively), whereas Kuru et al, Rosario et al, and Kamran et al reported FNR (false‐negative rates) lower than found in our data (4.3%, 3.6%, and 1.3%, respectively). Other studies have shown similar findings which were either higher or lower than the findings on the false negative rates in our study Porterfield et al, Shrestha et al, Carrillo et al, and Meko and Norton .…”
Section: Discussioncontrasting
confidence: 88%
“…Six studies recommended surgery [911,13,19,25] or repeat FNA [10] for large thyroid nodules even after benign FNA results because of a high false-negative rate (FNR) of 7.7–25.0%. In contrast to those studies, the remainder studies mentioned that large size itself should not be an indication for surgery because the FNR was within an acceptable range of 0.7–3.6% [20, 22, 24, 26] or not different from that of smaller nodules despite having a high FNR of 4.3–15.0% [8, 12, 21, 23]. In the present study, the FNR of large thyroid nodules with benign cytology was 3.6% (23 of all 632 nodules including follow-up nodules) to 13.4% (22 of 164 resected nodules) which was higher than the Bethesda recommendation of 0–3%.…”
Section: Discussionmentioning
confidence: 99%
“…FNA is the best available method to distinguish between benign and malignant lesions (5), even in the case of nodules smaller than 1 cm (3) or larger than 4 cm (38). In addition, FNA is an easy and low-cost outpatient procedure that is virtually devoid of serious complications.…”
Section: When Is a Fine Needle Aspiration Biopsy Indicated?mentioning
confidence: 99%